Biologically Active Components and Skincare Benefits of Rice Fermentation Products: A Review - Fan Yang; Yawen Hu; Meihui Wu; Miao Guo; Hua Wang (Cosmetics)
With the growing demand for environmental sustainability, the cosmetics industry is increasingly turning to natural ingredients with high bioactivity and efficacy. Rice, a staple food in many cultures, particularly in Asia, is renowned for its nutritional and medicinal benefits, as well as its skincare properties. Numerous studies have emphasized the multifunctional benefits of rice in skincare, ranging from its ability to enhance hydration to its effectiveness in addressing signs of aging, positioning it as a promising ingredient in cosmetic formulations. Recently, fermentation has emerged as an innovative technique that significantly enhances the bioactive potential of rice. This process amplifies the production of beneficial compounds, such as organic acids, amino acids, polyphenols, polysaccharides, vitamins, and minerals. Previous studies have shown that rice fermentation products (RFPs) exhibit a range of skincare benefits, including moisturization, antioxidation, anti-inflammation, whitening, and anti-aging effects. This review provides an overview of the fermentation process and advantages of RFPs, followed by a detailed analysis of their key bioactive components and the diverse skincare benefits they offer. Moreover, we discuss the challenges related to the standardization, component analysis, and efficacy evaluation of these products, and we conclude with potential future research directions to fully explore the skincare potential of RFPs.